Toxic stress and burnout: John Henryism and social dominance in the laboratory and STEM workforce - Rolle, Tiffany; Vue, Zer; Murray, Sandra A; Shareef, Salma Ash; Shuler, Haysetta D; Beasley, Heather K; Marshall, Andrea G; Hinton, Antentor (Pathogens and disease, 2021)
ABSTRACT Persons Excluded from science because of Ethnicity and Race (PEERs) face chronic exposure to interpersonal stressors, such as social discrimination, throughout their scientific careers, leading to a long-term decline in physical and mental health. Many PEERs exhibit John Henryism, a coping mechanism to prolonged stress where an individual expends higher levels of effort and energy at the cost of their physical and mental health. In this article, we discuss how social dominance may increase John Henryism within the STEM community; the causes, effects and costs of John Henryism; and highlight solutions to combat these social adversity stressors within the academic institution. We discuss the effects, causes and solutions to combatting John Henryism within the STEM community.